2022
DOI: 10.3390/su142114538
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge or Responsibility? The Role of Media Use on Citizens’ Willingness to Pay for Environment Governance

Abstract: It is not that the public is unwilling to participate in environmental protection, but rather that they lack the appropriate information. The media offers an alternative explanatory pathway to understanding citizens’ willingness to pay (WTP) for environmental governance, but the existing literature still lacks empirical studies on this topic and the intermediate mechanisms. Adopting an environmental communication perspective, this paper divided the environmental effects of media into two dimensions: knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…The messages conveyed through these mediums also resonate with the daily experiences of pesantren communities accustomed to low-technology environments. Previous research has further validated that the utilisation of traditional media tends to be more efficacious in fostering effective environmental communication (Wang, 2022).…”
Section: Objectification Of Ecological Piety In the Eco-pesantrenmentioning
confidence: 90%
See 3 more Smart Citations
“…The messages conveyed through these mediums also resonate with the daily experiences of pesantren communities accustomed to low-technology environments. Previous research has further validated that the utilisation of traditional media tends to be more efficacious in fostering effective environmental communication (Wang, 2022).…”
Section: Objectification Of Ecological Piety In the Eco-pesantrenmentioning
confidence: 90%
“…Once internalised, these personal norms tend to govern an individual's behaviour. Instances of transgressions against these personal norms may not invariably be identified or socially censured, but such deviations typically evoke feelings of guilt that prompt immediate correction (Wang, 2022).…”
Section: The Understanding Of Kyai On Fiqh Al-bī'ah In Environmental ...mentioning
confidence: 99%
See 2 more Smart Citations
“…This (lack of) feeling of responsibility also influences consumers' WTP. Wang (2022) found that individuals who feel an environmental responsibility have a higher WTP for improvements to the environment.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%